Understanding Jordanian Psychiatric Nurses’ Smoking Behaviors: A Grounded Theory Study - Khaldoun M. Aldiabat; Michael Clinton (Nursing Research and Practice)
Purpose. Smoking is prevalent in psychiatric facilities among staff and patients. However, there have been few studies of how contextual factors in specific cultures influence rates of smoking and the health promotion role of psychiatric nurses. This paper reports the findings of a classical grounded theory study conducted to understand how contextual factors in the workplace influences the smoking behaviors of Jordanian psychiatric nurses (JPNs). Method. Semi-structured individual interviews were conducted with a sample of eight male JPNs smokers at a psychiatric facility in Amman, Jordan. Findings. Constant comparative analysis identified becoming a heavy smoker as a psychosocial process characterized by four sub-categories: normalization of smoking; living in ambiguity; experiencing workplace conflict; and, facing up to workplace stressors. Conclusion. Specific contextual workplace factors require targeted smoking cessation interventions if JPNs are to receive the help they need to reduce health risks associated with heavy smoking.